RELATIONSHIP WORD OF MOUTH, ADVERTISING AND PRODUCT QUALITY TO BRAND AWARENESS - Mahaputra, M. Ridho; Saputra, Farhan (Dinasti Publisher, 2021)
This article is a scientific article that aims to hypothesize the influence of research between variables that will be used in further research, within the scope of Marketing Management. The method of writing this Literature Review article is using the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this study are: 1) Word of mouth is related to Brand Awareness; 2) Advertising relates to Brand Awareness; and 3) Product Quality is related to Brand Awareness. In addition to these 3 exogenous variables that affect the endogenous variable Brand Awareness, there are many other factors including Price Perception, Brand Image and Product Design variables.